Pengaruh Media Pembelajaran (Bingo dan Textbook) dan Perbedaan Usia terhadap Pemahaman Kosakata Bahasa Inggris - Hana Nurwahidah Sudrajat; Firmanul Catur Wibowo; Juhana Juhana; Yus Alvar Saabighoot (Syntax Corporation Indonesia, 2024)
This study was conducted to determine the effect of learning media (bingo and textbook) and age differences on understanding English vocabulary. It aims to determine the effectiveness of the use of learning media on understanding English vocabulary based on age differences. This study was structured using an experimental design because it was carried out directly and the results obtained directly from field data. The sample used in this study was taken from 32 students aged over 9 years and 32 students aged less than 9 years. The independent variables in this study were learning media (bingo and textbook) and age differences. While the dependent variable is the understanding of English vocabulary. Measurement of vocabulary comprehension was done using descriptive statistical methods. The software used for data analysis is SPSS. To determine the results in this study using Two Way Anova if there is an interaction between two independent variables on the dependent variable. The results of data analysis show that there are differences in understanding of English vocabulary between students who use bingo and textbook learning media with significant results. The Middle Value Line Fcount = 7.932 and FTable = 4.001 which implies that there are differences in the understanding of English vocabulary of students aged over nine years and less than nine years. The conclusion of this study is the use of learning media (bingo and textbook) and the difference in age have an influence on the understanding of English vocabulary in third grade students.